2023
DOI: 10.1186/s12889-023-15208-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between novel anthropometric indices and the incidence of hypertension in Chinese individuals: a prospective cohort study based on the CHNS from 1993 to 2015

Abstract: Background: Recently, novel anthropometric indices (AHIs), including the body roundness index (BRI) and a body shape index (ABSI), were proposed to evaluate a subject’s nutritional status and metabolic disorders. In the present study, we mainly analyzed the relationship between AHIs and the incidence of hypertension and preliminarily compared their abilities to discriminate hypertension incidence in the Chinese population from the China Health and Nutrition Survey (CHNS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Zhang et al . [ 35 ] found that the risk of hypertension increases with the increase of ABSI and BRI in Chinese individuals. Additoanlly, BRI was found to be superior to ABSI in identifying new-onset hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al . [ 35 ] found that the risk of hypertension increases with the increase of ABSI and BRI in Chinese individuals. Additoanlly, BRI was found to be superior to ABSI in identifying new-onset hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…New-onset hypertension was assessed based on a combination of blood pressure, medical history, and medication information, that is, SBP ≥ 140 mmHg and/or diastolic blood pressure (DBP) ≥ 90 mmHg or diagnosed by a physician or under antihypertensive treatment during the follow-up ( 26 ). All participants were asked to sit and rest for at least 10 min before taking blood pressure measurements, then three blood pressure measurements were taken by trained staff according to the standard protocol and using a suitable cuff and mercury sphygmomanometer, with at least 1 min between measurements ( 27 , 28 ). In this study, the values of SBP and DBP were obtained by averaging the three blood pressure measurements.…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%